2020
DOI: 10.18203/2320-1770.ijrcog20202729
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome in pregnancy with thrombocytopenia

Abstract: Background: Thrombocytopenia is second most common haematological abnormality in pregnancy after anemia. The aim of this study was to find out the prevalence, causative factor of thrombocytopenia and to observe the obstetrics outcome of pregnancies complicated with thrombocytopenia.Methods: This is prospective study of maternal outcome in pregnancy with thrombocytopenia carried out at tertiary care center from February 2019 to January 2020. Out of 350 antenatal screened women, 25 women who were diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
7
0
1
Order By: Relevance
“…In the present study, the mean age was 25.33±2.90 years and out of 150 women, 91 (60.7% of enrolled women) were living in rural areas. These observations were comparable to the study conducted by Sojitra et al [ 5 ]. Whereas in another study conducted by Gebreweld et al, the mean age was reported higher i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the mean age was 25.33±2.90 years and out of 150 women, 91 (60.7% of enrolled women) were living in rural areas. These observations were comparable to the study conducted by Sojitra et al [ 5 ]. Whereas in another study conducted by Gebreweld et al, the mean age was reported higher i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, Mean gestational age was 38.42 ± 1.69 weeks which was similar to studies conducted by Chauhan V et al [7] (38.6 ± 1.34weeks), Sojitra M et al [4] (38 weeks) and Lin et al [8] (39 weeks). Where as in the study by Bouzari et al [9] the mean age was 35.83 ± 3.61 weeks which was lower than our study.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, Prevalence of thrombocytopenia was 6.67% which was comparable to study done by Sojitra M et al [4] (7.1%), Vyas et al [5] (7.6%), Burrows et al [6] (7.6%) and Chauhan V et al [7] (8.4%). Our prevelance was lower than other studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations